Astrocyte ryanodine receptors facilitate gliotransmission and astroglial modulation of synaptic plasticity - Lalo, Ulyana; Pankratov, Yuriy (Frontiers in Cellular Neuroscience, 2024)
Intracellular Ca 2+ -signalling in astrocytes is instrumental for their brain "housekeeping" role and astroglial control of synaptic plasticity. An important source for elevating the cytosolic Ca 2+ level in astrocytes is a release from endoplasmic reticulum which can be triggered via two fundamental pathways: IP3 receptors and calcium-induced calcium release (CICR) mediated by Ca 2+ -sensitive ryanodine receptors (RyRs). While the physiological role for glial IP3 became a focus of intensive research and debate, ryanodine receptors received much less attention.We explored the role for ryanodine receptors in the modulation of cytosolic Ca 2+ -signalling in the cortical and hippocampal astrocytes, astrocyte-neuron communication and astroglia modulation of synaptic plasticity. Our data show that RyR-mediated Ca 2+ -induced Ca 2+ -release from ER brings substantial contribution into signalling in the functional microdomains hippocampal and neocortical astrocytes. Furthermore, RyR-mediated CICR activated the release of ATP and glutamate from hippocampal and neocortical astrocytes which, in turn, elicited transient purinergic and tonic glutamatergic currents in the neighbouring pyramidal neurons. The CICR-facilitated release of ATP and glutamate was inhibited after intracellular perfusion of astrocytes with ryanodine and BAPTA and in the transgenic dnSNARE mice with impaired astroglial exocytosis. We also found out that RyR-mediated amplification of astrocytic Ca 2+signalling enhanced the long-term synaptic potentiation in the hippocampus and neocortex of aged mice.Combined, our data demonstrate that ryanodine receptors are essential for astrocytic Ca 2+signalling and efficient astrocyte-neuron communications. The RyR-mediated CICR contributes to astrocytic control of synaptic plasticity and can underlie, at least partially, neuroprotective and cognitive effects of caffein.Astrocytes are an instrumental component of brain cellular networks. Apart from generally acknowledged brain "housekeeping" functions, such as metabolic and structural support of neurons and control of neuro-vascular interface, astrocytes have recently been implicated into higher brain functions, like information processing and learning and memory (